The relationship between the teacher`s teaching techniques and the spoken english language proficiency reached by the students who have finished Advanced English II at the Department of Foreign Languages at the University of El Salvador, 2015 - Ayala Cáceres, Mercedes Margarita
The purpose of this study was to find out the relationship between the teachers’ teaching techniques and the proficiency reached by the students. The population of this study involved all the students who have finished Advanced English II, at the Foreign Language Department, at the University of El Salvador, by semester II, 2015. Forty students were taken randomly as the sample of the study. The type of study used in this research was correlational. The data was collected through a questionnaire. The results indicated that some English teachers at the Foreign Language Department have made a good used of controlled, semi controlled and free techniques because the majority of the students under study had a very good level of proficiency and they were exposed to those techniques frequently.